Mapping adolescent reward anticipation, receipt, and prediction error during the monetary incentive delay task. Issue 1 (21st September 2018) - Cao, Zhipeng; Bennett, Marc; Orr, Catherine; Icke, Ilknur; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Bromberg, Uli; Büchel, Christian; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; et al.
Abstract: The functional neuroanatomy and connectivity of reward processing in adults are well documented, with relatively less research on adolescents, a notable gap given this developmental period's association with altered reward sensitivity. Here, a large sample ( n  = 1, 510) of adolescents performed the monetary incentive delay (MID) task during functional magnetic resonance imaging. Probabilistic maps identified brain regions that were reliably responsive to reward anticipation and receipt, and to prediction errors derived from a computational model. Psychophysiological interactions analyses were used to examine functional connections throughout reward processing. Bilateral ventral striatum, pallidum, insula, thalamus, hippocampus, cingulate cortex, midbrain, motor area, and occipital areas were reliably activated during reward anticipation. Bilateral ventromedial prefrontal cortex and bilateral thalamus exhibited positive and negative activation, respectively, during reward receipt. Bilateral ventral striatum was reliably active following prediction errors. Previously, individual differences in the personality trait of sensation seeking were shown to be related to individual differences in sensitivity to reward outcome. Here, we found that sensation seeking scores were negatively correlated with right inferior frontal gyrus activity following reward prediction errors estimated using a computational model. Psychophysiological interactions demonstrated widespread cortical and subcortical connectivity during reward processing, including connectivity between reward‐related regions with motor areas and the salience network. Males had more activation in left putamen, right precuneus, and middle temporal gyrus during reward anticipation. In summary, we found that, in adolescents, different reward processing stages during the MID task were robustly associated with distinctive patterns of activation and of connectivity.